전기자동차용 OBC 일체형 1.5㎾급 LDC 컨버터에 대한 연구 - 김형식(Hyung-Sik Kim); 전준혁(Joon-Hyeok Jeon); 김희준(Hee-Jun Kim); 안준선(Joon-Seon Ahn) (한국정보전자통신기술학회 논문지, 2019)
PHEV(Plug in Hybrid Electric Vehicle)와 BEV(Battery Electric Vehicle)는 모터 및 차량 전장 시스템의 구동을 위하여 고전압 배터리를 사용하며 이를 충전시켜주는 OBC(On-Board Charger)와 고전압에서 저전압으로 전력변환을 해주는 LDC(Low DC/DC Converter)가 반드시 필요하다. OBC와 LDC는 차량에 독립적인 시스템으로 동작 하며 개별 공간을 사용하기 때문에 이를 통합한 시스템을 활용하여 무게 및 사용 공간 확보에 대한 필요성이 대두 되고 있다. 본 논문은 LDC 트랜스포머의 설계를 단순화하여 절연형 전류원 컨버터를 사용한 OBC에 통합이 가능한 1.5㎾급 LDC컨버터에 대하여 제안하였다. 제안된 LDC는 양방향 벅-부스트 컨버터의 고정된 임의의 출력 전압을 사용하여 LDC의 최종 출력 전압의 제어가 가능하기 때문에 기존의 OBC-LDC 통합 시스템과 비교하여 배터리 전압 사용 범위, 컨버터의 Duty Ratio 및 OBC의 출력 턴 비를 고려한 트랜스포머 설계에 대한 부분을 단순화 할 수 있는 장점을 가지고 있다. 제안된 LDC의 시제품을 제작하여 200V ~ 400V의 입력 전압에서 정상 동작을 확인 하였으며 정격 부하 조건에서 최대 효율 91.885%를 달성 하였다. 또한 OBC-LDC통합 시스템 구축을 통해 약 6.51L의 부피를 달성 하였으며 기존 독립적인 시스템에 비해 15.6% 저감되어 공간 확보에 대한 이점을 확인 할 수 있었다. PHEV(Plug in Hybrid Electric Vehicle) and BEV(Battery Electric Vehicle) equip high voltage batteries to drive motor and vehicle electric system. Those vehicle require OBC(On-Board Charger) for charging batteries and LDC(Low DC/DC Converter) for converting from high voltage to low voltage. Since the charger and the converter actually separate each other in electrical vehicles, there is a margin to reduce the vehicle weight and area of installation by integration two systems. This paper studies a 1.5kW LDC converter that can be integrated into an OBC using an isolated current-fed converter by simplifying the design of LDC transformers. The proposed LDC can control the final output voltage of the LDC by using a fixed arbitrary output voltage of the bidirectional buck-boost converter, so that Compared to the existing OBC-LDC integrated system, it has the advantage of simplifying the transformer design considering the battery voltage range, converter duty ratio and OBC output turn ratio. Prototype of the proposed LDC was made to confirm normal operation at 200V ~ 400V input voltage and maximum efficiency of 91.885% was achieved at rated load condition. In addition, the OBC-LDC integrated system achieved a volume of about 6.51L and reduced the space by 15.6% compared to the existing independent system. KCI Citation Count: 0